Performance Of General Criminal Employees At The State Prosecutor's Office Of Bengkulu - Cristina Rumondang; Asnawati Asnawati; Antonio Imanda (Professional: Jurnal Komunikasi dan Administrasi Publik, 2022)
This study aims to determine the performance of General Crime employees at Bengkulu Prosecutor’s Office in resolving General Crime Cases. This study uses a qualitative method. The data were collected using observation, interview, and documentation techniques with the theory of performance indicators Robbins (2016:260). Based on the results of the study, it can be seen that the Performance of General Crime Officers at Bengkulu Prosecutor's Office are: (1) The quality is in accordance with the rules and standard operating procedures (SOP). (2) The quantity in carrying out the work has a report completion target. (3) The timely completion of a general criminal case received is 30 days from the receipt of the SPDP and 20 days to complete the file, then the case file is immediately registered with the Court. (4) The effectiveness of officers with educational backgrounds in the General Crimes Division at Bengkulu Prosecutor's Office varies from high school and SI graduates, and the existing facilities and infrastructure are adequate and support the employee's work process. (5) The independence; 21 employees consist of 8 prosecutors, 8 administrative employees, and 5 honorary employees, all of whom have carried out their duties and functions in accordance with the existing SOPs.